Capgras Syndrome and Unilateral Spatial Neglect in Nonconvulsive Status Epilepticus - L. Christine Turtzo; Jonathan T. Kleinman; Rafael H. Llinas (Behavioural Neurology)
Nonconvulsive status epilepticus can manifest as personality changes and psychosis. We report an 87-year-old right-handed male presenting with both Capgras syndrome and severe unilateral spatial neglect during nonconvulsive status epilepticus. After treatment of his seizures, his Capgras syndrome and hemispatial neglect resolved. This case illustrates a report of the confluence of Capgras syndrome and documented hemispatial neglect in nonconvulsive status epilepticus only reported once previously [1].